Parton distribution functions at LO, NLO and NNLO with correlated uncertainties between orders - Belov, P; Britzger, D; Camarda, S; Cooper-Sarkar, A; Diaconu, C; Feltesse, J; Gizhko, A; Glazov, A; Kolesnikov, V; Lohwasser, K; Luszczak, A; Myronenko, V; et al. (Springer New York LLC, 2014)
Sets of parton distribution functions (PDFs) of the proton are reported for the leading (LO), next-to-leading (NLO) and next-to-next-to-leading-order (NNLO) QCD calculations. The parton distribution functions are determined with the HERAFitter program using the data from the HERA experiments and preserving correlations between uncertainties for the LO, NLO and NNLO PDF sets. The sets are used to study cross-section ratios and their uncertainties when calculated at different orders in QCD. A reduction of the overall theoretical uncertainty is observed if correlations between the PDF sets are taken into account for the ratio of (Equation Present) di-boson to (Equation Present) boson production cross sections at the LHC.